The world between the wars, 1919-39 : an economist's view - Davis, Joseph Stancliffe (Baltimore : Johns Hopkins University Press, 1975)
American policies of neutrality, isolationism, and internationalism in decades after World War I. Depression and the world order. Rise of totalitarian regimes in Europe and Asia; their expansionist ambitions. American response to war in Europe. Japanese attack Pearl Harbor.
Includes bibliographical references and index.
aia 11/10/2018
Loan
Keywords: Economic history; Depressions; Business cycles